Decoding the Specificity of Post-Error Adjustments Using EEG-Based Multivariate Pattern Analysis - Li, Qing; Wang, Jing; Li, Zhifang; Chen, Antao (The Journal of neuroscience, 2022)
Errors can elicit post-error adjustments that serve to optimize performance by preventing further errors. An essential but unsolved issue is that whether post-error adjustments are domain-general or domain-specific, which was investigated in the present study through eliciting different types of errors. Behavioral and electrophysiological data were recorded when male and female subjects performed the Eriksen flanker task. For this study, we examined the aforementioned issue by combining event-related potential and multivariate pattern analysis. The results indicated that post-error slowing, error-related negativity, and error positivity were comparable between congruent and incongruent errors, indicating that errors triggered domain-general interference mechanisms. Whereas post-error accuracy and late positive potential elicited by incongruent errors were larger than those elicited by congruent errors, exhibiting domain-specific control adjustment mechanisms. Importantly, no successful decoding soon after errors was found between congruent and incongruent errors, but above-chance decoding was observed between these two types of errors with increasing time, which further support that domain-general adjustments occurred in the early stage, whereas domain-specific adjustments appeared in the late stage. Furthermore, brain-behavior correlation results suggested that the late post-error adjustments predicted subsequent behavior performance. Taken together, this study revealed that early domain-general interference adjustments induced by errors are reflected in error detection and error awareness, which are independent of error types; on the contrary, late domain-specific control adjustments are reflected in attentional adjustments, which are modulated by error types. To date, clear evidence on the specificity of post-error adjustments is lacking. The present study provides neurophysiological evidence that post-error adjustments simultaneously rely on both domain-general and domain-specific mechanisms. Event-related potential results indicated that domain-general adjustments were accompanied by the interference of error detection and error awareness. In contrast, domain-specific adjustments were associated with attentional adjustments. Multivariate pattern analysis further decoded the two features of post-error adjustments in the early stage matching the time patterns of error-related negativity and error positivity and in the late stage corresponding to the late positive potential. Temporal generalization analysis showed that domain-specific processing appeared stably in late post-error adjustments. Hence, we propose that post-error different stages may determine the specificity of post-error adjustments.